Assessing the intestinal carriage rates of vancomycin-resistant enterococci (VRE) at a tertiary care hospital in Hungary - Franyó, Dorottya; Kocsi, Balázs; Bukta, Evelin Erzsébet; Szabó, Judit; Dombrádi, Zsuzsanna (Folia microbiologica, 2020)
Excessive use of antibiotics contributes to the selection of resistant bacteria and intestinal colonization with multiresistant pathogens poses a risk factor for subsequent infections. The present study assessed vancomycin-resistant enterococci (VRE) carriage rates in patients admitted to our tertiary care hospital. Stool samples sent for routine culturing were screened with vancomycin containing solid or broth enrichment media. VRE isolates were identified with matrix-assisted laser desorption/ionization-time of flight mass spectrometry and antibiotic susceptibilities were tested by E-test. Vancomycin resistance genes were detected by polymerase chain reaction. Medical records of carriers were examined for suspected risk factors for colonization. Altogether 3025 stool specimens were analyzed. Solid media identified a VRE carriage rate of 2.2% while broth enrichment detected 5.8%. Seventy percent of the isolates were Enterococcus faecium. VanB genotype was detected in 38.2%, VanA in 37.3%, VanC1 in 22.6%, and VanC2 in 1.9%. All VRE were sensitive to linezolid, daptomycin, and tigecycline. Collective risk factors for carriage were diabetes, normal flora absence, Clostridioides difficile positivity, longer hospital stay, and advanced age. 78.5% of the carriers received antibiotic therapy which was metronidazole in most cases (47.3%). We recommend regular screening of risk groups such as patients with diabetes, history of recent hospitalization, or former C. difficile infection as an imperative step for preventing VRE dissemination.
Keywords: dospělí; Intestines; Genotype; Female; feces; Feces; mikrobiální testy citlivosti; dítě; předškolní dítě; Risk factors; Adult; ženské pohlaví; mladý dospělý; Adolescent; Carrier State; Tertiary Care Centers; lidé; centra terciární péče; genotyp; Anti-Bacterial Agents; MALDI-TOF; Aged, 80 and over; VRE carriage; PCR; grampozitivní bakteriální infekce; Risk Factors; střeva; retrospektivní studie; Microbial Sensitivity Tests; přenašečství; Vancomycin Resistance; Vancomycin-Resistant Enterococci; Gram-Positive Bacterial Infections; Male; Aged; Child, Preschool; Young Adult; rizikové faktory; Hungary; lidé středního věku; Child; senioři nad 80 let; senioři; mužské pohlaví; Maďarsko; antibakteriální látky; Antibiotic resistance; Retrospective Studies; enterokoky rezistentní vůči vankomycinu; Middle Aged; mladiství; rezistence na vankomycin; Humans